Enhancing argumentation and decision‑making of preservice early childhood education teachers through role‑playing on animal experimentation - Vicente, Juan José; Franco-Mariscal, Antonio Joaquín; Oliva, José María (Springer, 2024)
This study explores the socio-scientific issue of the relevance of animal experimentation using a role-playing game to develop argumentation and decision-making skills as key components of critical thinking. The activity was conducted with two cohorts, each con- sisting of 30 pre-service early childhood education teachers at the University of Málaga (Málaga, Spain). The study analyzes the arguments provided by the participants to justify their decisions and perceptions on the issue before and after engaging in the role-playing. The findings reveal a progression of participants from the initial rejection of animal exper- imentation to recognizing its imperative role in shaping scientific knowledge. Addition- ally, an enhancement in the understanding of rational aspects of the issue is detected, as observed through the evolution of the types of arguments employed in justifications before and after the intervention. Furthermore, emotionally charged arguments related to ethical and moral aspects of the issue are also observed.
Keywords: Educación infantil; Juegos de rol; Profesores - Formación profesional; Experimentación animal; Early Childhood Education; Teachers; Role-Playing; Animal Experimentation